Digital Screen Time Limits and Young Children's Psychological Well‐Being: Evidence From a Population‐Based Study. Issue 1 (13th December 2017) - Przybylski, Andrew K.; Weinstein, Netta
Abstract : There is little empirical understanding of how young children's screen engagement links to their well‐being. Data from 19, 957 telephone interviews with parents of 2‐ to 5‐year‐olds assessed their children's digital screen use and psychological well‐being in terms of caregiver attachment, resilience, curiosity, and positive affect in the past month. Evidence did not support implementing limits (< 1 or < 2 hr/day) as recommended by the American Academy of Pediatrics, once variability in child ethnicity, age, gender, household income, and caregiver educational attainment were considered. Yet, small parabolic functions linked screen time to attachment and positive affect. Results suggest a critical cost–benefit analysis is needed to determine whether setting firm limits constitutes a judicious use of caregiver and professional resources.